The Whilton dispute, 1264-1380 : a social-legal study of dispute settlement in medieval England - Palmer, Robert C., 1947- (Princeton, N.J. : Princeton University Press, 1984)
Robert C. Palmer examines the Whilton dispute, an intrafamilial, multigenerational contest over a large estate that continued, primarily in the courts, from 1264until 1380. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- Table of Documents -- Preface -- Abbreviations -- A Whilton Dispute Chronology -- CHAPTER 1. Introduction -- CHAPTER 2. The Origins of the Dispute -- CHAPTER 3. The Assize of Novel Disseisin and the Attaint -- CHAPTER 4. The Writ of Entry and the Writ Certiorari -- CHAPTER 5. Securing Title to Whilton -- CHAPTER 6. Litigation by Writ of Right -- CHAPTER 7. The Interlude -- CHAPTER 8. Resumption and Compromise -- CHAPTER 9. Formedon and the Use -- CHAPTER 10. Conclusions -- APPENDIX 1. Auxiliary Documents -- APPENDIX 2. Statutes -- APPENDIX 3. Glossary of Legal Terms -- Notes -- Index.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: De Whelton, William, -- -1267 -- Estate; Whilton family; Mortimer family; Whilton family; De Whelton, William, -- -1267 -- Estate; De Whelton, William, -- m. 1267 -- Patrimoine; Whelton (Famille); Mortimer (Famille); Mortimer family; De Whelton, William, -- -1267; Whilton family; Real property -- England -- History -- To 1500.; Great Britain -- History -- Medieval period, 1066-1485.; Sociological jurisprudence -- England -- History -- To 1500.; Real property -- England -- History; Biens réels -- Angleterre -- Histoire; Grande-Bretagne -- Histoire -- 1066-1485 (Moyen Âge); LAW -- Administrative Law & Regulatory Practice; Decedents' estates; Real property; Sociological jurisprudence; England; Great Britain; Eigendomsrecht; Conflictmanagement; Processen (rechtspraak); To 1500; England -- Real property -- Law, 1154-1399 - Cases; History